Interleukin-8 levels in children with bacterial, tuberculous and aseptic meningitis - Yilmaz, Erdal; Gürgöze, M. Kaya; Ilhan, Nevin; Doğan, Yasar; Aydinoğlu, Hakan (The Indian Journal of Pediatrics, 2002)
Objective : Interleukin-8 (IL-8) is produced in monocytes and vascular endothelial cells in response to stimulation with bacteria or lipopolysaccharides, and is released from these cells into blood stream or tissue fluid. Methods : Cerebrospinal fluid (CSF) levels of interleukin-8 in 56 children with nonbacterial, bacterial and tuberculous meningitis (TBM), and in 15 control subjects were analyzed to evaluate the involvement of this cytokine in the pathogenesis acute bacterial meningitis and their discriminative value between different etiologies of meningitis. The kinetics of IL-8 concentrations during the course of bacterial meningitis was also evaluated in patients. IL-8 levels were significantly higher in bacterial and TBM than in aseptic meningitis and in control subjects (p<0.0001). Results : There was no difference in the levels of IL-8 between the non-bacterial meningitis and control groups. The analysis of the kinetics of production of IL-8 in patients with bacterial meningitis showed that the SSF concentrations of this cytokine decreased to undetectable values in recovery stage. Conversely in patients with TBM the concentrations of IL-8 were elevated in two weeks after beginning the specific treatment. Conclusion : The results suggest that determining IL-8 levels may be useful in the differential diagnosis.
Keywords: Aseptic meningitis; Bacterial meningitis; IL-8